2012
DOI: 10.7150/ijbs.3796
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Garlic Oil on Hepatocarcinoma Induced by N-Nitrosodiethylamine in Rats

Abstract: To investigate the protective effects and the possible mechanisms of garlic oil (GO) against N-nitrosodiethylamine (NDEA)-induced hepatocarcinoma in rats, Wistar rats were gavaged with GO (20 or 40 mg/kg) for 1 week, and then were gavaged with GO and NDEA (10 mg/kg) for the next 20 weeks. The changes of morphology, histology, the biochemical indices of serum, and DNA oxidative damage of liver were examined to assess the protective effects. Lipid peroxidation (LPO), antioxidant defense system, and apoptosis-rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
64
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(70 citation statements)
references
References 69 publications
6
64
0
Order By: Relevance
“…Recently, it has been gradually understood that the latter are responsible for anticancer effects exerting through multiple mechanisms such as: amelioration of oxidative stress and improvement of immune function (Butt at al., 2009), and inhibition of metabolic carcinogenic activation (Miroddi at al., 2011;Velliyagounder et al, 2012;Wang et al, 2012;Zhang et al, 2012) Experiments in further had shown new mechanisms for the anticancer role of garlic oil such as by inducing apoptosis (Choi and Park, 2012;Wang et al, 2012), inhibiting differentiation, inhibiting tumor angiogenesis (Konkimalla et al, 2008), and reversing multidrug resistance (Arora et al, 2004). As compounds, it has been demonstrated that garlic oil has the ability to enhance the absorption of its main active component (Amagase et al, 2001).…”
Section: Effects Of Garlic Oil Onmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it has been gradually understood that the latter are responsible for anticancer effects exerting through multiple mechanisms such as: amelioration of oxidative stress and improvement of immune function (Butt at al., 2009), and inhibition of metabolic carcinogenic activation (Miroddi at al., 2011;Velliyagounder et al, 2012;Wang et al, 2012;Zhang et al, 2012) Experiments in further had shown new mechanisms for the anticancer role of garlic oil such as by inducing apoptosis (Choi and Park, 2012;Wang et al, 2012), inhibiting differentiation, inhibiting tumor angiogenesis (Konkimalla et al, 2008), and reversing multidrug resistance (Arora et al, 2004). As compounds, it has been demonstrated that garlic oil has the ability to enhance the absorption of its main active component (Amagase et al, 2001).…”
Section: Effects Of Garlic Oil Onmentioning
confidence: 99%
“…How garlic oil exhibits its effect on the tumor cells and its underlying mechanism are poorly understood (Agarwal at al., 2007;Zhang at al., 2012), especially the effect on pancreatic carcinoma. For this reason, the aim of this study is to investigate the effect of garlic oil on human pancreatic cancer cells (including AsPC-1, PANC-1, and Mia PaCa-2 cell lines) and its underlying mechanism in order to find a pathway for pancreatic cancer prevention and treatment considering its multidrug resistance.…”
Section: Effects Of Garlic Oil Onmentioning
confidence: 99%
“…Given that tubular cells are very susceptible to ROS (20)(21)(22), renal tubular apoptosis is a characteristic feature for the progression of IR insult (23).…”
mentioning
confidence: 99%
“…Many investigations are now being carried out to discover naturally occurring compounds which can suppress or prevent the process of carcinogenesis. 3,4 Epidemiological studies continue to support the premise that dietary intake of Allium vegetables such as garlic may reduce the risk of different types of malignancies, included tumors of the liver, 5 lung, 6 skin, 7 stomach in rodents. 8 The protective effect against cancer of Allium vegetables is attributed to organosulfur compounds (OSC) including diallyl sulfide, diallyl disulfide (DADS), and/or diallyl trisulfide (DATS).These compounds have an immunomodulatory effect.…”
Section: Introductionmentioning
confidence: 99%
“…These findings were similar to those obtained by Khan and Sultana,31 who recorded that Nigella sativa is a potent chemopreventive agent and suppresses Fe-NTA-induced oxidative stress, hyperproliferative response and renal carcinogenesis in Wistar rats. Garlic and its allyl sulfur may exert their protective effects on carcinogenesis in animal and in vitro by several mechanisms, including inhibition of carcinogen-induced DNA adduct formation, 32 blockage of cell growth, blockage of cell proliferation, and blockage of angiogenesis, 33 induction of differentiation and/or apoptosis, 5,34 enhancement of carcinogen-detoxifying enzymes, 35 and/or suppression of carcinogenactivating enzymes, 36 inhibition of cyclooxygenase-2 expression, 37 scavenging carcinogeninduced free radicals, 38,39 and inhibition of lipid peroxidation. 39,40 Another possible mechanism of cancer prevention and suppression of cancer progression is immune enhancement by garlic, 9 and Nigella sativa, 21 and these agreed with our hematologic and histopathological findings.…”
Section: Articlementioning
confidence: 99%